2007
DOI: 10.1073/pnas.0703944104
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of soluble guanylyl cyclase, the NO receptor, by S-nitrosylation

Abstract: The molecular mechanism of desensitization of soluble guanylyl cyclase (sGC), the NO receptor, has long remained unresolved. Posttranslational modification and redox state have been postulated to affect sGC sensitivity to NO but evidence has been lacking. We now show that sGC can be S-nitrosylated in primary aortic smooth muscle cells by S-nitrosocysteine (CSNO), an S-nitrosylating agent, in human umbilical vein endothelial cells after vascular endothelial growth factor treatment and in isolated aorta after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(136 citation statements)
references
References 38 publications
4
130
1
1
Order By: Relevance
“…Analysis of non-mammalian proteins that are structurally similar to GC in which Cys-122 is highly conserved has revealed that subtle conformational changes at Cys-122 may limit NO ⅐ binding at the sixth coordinating position of reduced heme (at His-105). This, in turn, would prevent the nitrosyl-heme formation that is necessary for GC activation (18,28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of non-mammalian proteins that are structurally similar to GC in which Cys-122 is highly conserved has revealed that subtle conformational changes at Cys-122 may limit NO ⅐ binding at the sixth coordinating position of reduced heme (at His-105). This, in turn, would prevent the nitrosyl-heme formation that is necessary for GC activation (18,28).…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed Mutagenesis and Transfection-Expression constructs in pCMV5 were used to overexpress ␣ 1 -, ␤ 1 -, and ␤ 1 -C122A subunits of rat GC as described previously (18). COS-7 cells, which do not express endogenous GC, were plated in 6-well tissue culture dishes and transfected with 5 g of DNA for 4 h with Lipofectamine 2000 TM (Invitrogen) (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include oxidation of sGC heme and subsequent protein degradation (51,52) and reduced sGC activity in response to S-nitrosylation (30,31). Although it is clear that these mechanisms play an important role in desensitization of sGC signaling under chronic oxidative conditions, their contribution to rapid desensitization of sGC in response to NO (46) is unclear.…”
mentioning
confidence: 99%